2014
DOI: 10.1007/s13146-014-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative and quantitative model for climate-driven lake formation on carbonate platforms based on examples from the Bahamian archipelago

Abstract: Lakes on carbonate platform islands such as the Bahamas display wide variability in morphometry, chemistry, and fauna. These parameters are ultimately driven by climate, sea level, and carbonate accumulation and dissolution. The authors propose a model that integrates climatological, geomorphological, and stratigraphic frameworks to understand processes of carbonate-hosted lake formation and limnological characteristics in modern day environments, with applications to carbonate lake sedimentary records. Fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These sulfides, which are absent in the Big Pond mats, may be attributed to a late-stage remobilization of progressively degraded organic matter and metal-bearing sulfides attending late diagenesis and/or metamorphic overprint. Accordingly, it is suggested that the metal distribution patterns reported for the Big Pond samples may be intrinsic to the formation and early diagenetic evolution of microbial mats in general, or at least to those associated with CaCO 3 stromatolitic constructions formed in hypersaline shallow marine and/or lake environments as reported for Big Pond (Park-Boush et al, 2014) and…”
Section: Keys To Understand the Fossil Recordmentioning
confidence: 79%
See 2 more Smart Citations
“…These sulfides, which are absent in the Big Pond mats, may be attributed to a late-stage remobilization of progressively degraded organic matter and metal-bearing sulfides attending late diagenesis and/or metamorphic overprint. Accordingly, it is suggested that the metal distribution patterns reported for the Big Pond samples may be intrinsic to the formation and early diagenetic evolution of microbial mats in general, or at least to those associated with CaCO 3 stromatolitic constructions formed in hypersaline shallow marine and/or lake environments as reported for Big Pond (Park-Boush et al, 2014) and…”
Section: Keys To Understand the Fossil Recordmentioning
confidence: 79%
“…5-10 m high) covered with vegetation. Big Pond has been cut off from any surface exchange with the ocean for approximately 4,000 years and functioned as a lake since then (Park-Boush, Myrbo, & Michelson, 2014;Park-Boush, pers. comm.).…”
Section: Geological Setting and Sample Descriptionmentioning
confidence: 99%
See 1 more Smart Citation